PENGEMBANGAN DATA BASE BERBASIS SISTEM INFORMASI GEOGRAFIS JALAN NASIONAL (SIG-JN) (Studi Kasus : Jalan Nasional Provinsi Sulawesi Barat) - , Rozaidil Ridwan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Road Infrastructure Management is needed to guarantee the service life of the road and to conform initial design of service life. Based on the Decree of the Ministry of Public Works Number : 631/KPTS/M/2009, national road asset in West Sulawesi Province is as many as 28 roads with a total length of 571,981 km. The Agency which is directly responsible to the National Road in West Sulawesi Province is SNVT P2JN Sulbar. In order to facilitate and to accelerate the decision-making of information in road management, it would be required an application based on Geographic Information System of National Road in West Sulawesi Province. National Road Geographic Information System (SIG-JN) was developed by creating spatial data using Quantum GIS program, WebGIS development with Mapserver program, web programming using PHP, and database management using MySQL. SIG-JN is designed by displaying two interfaces, which are users and admin. SIG-JN is applied to all national roads in West Sulawesi Province using data survey in 2012. Mapping of visual overview of road conditions at each interval of 0.1 km based on the value of roughness (IRI) can be obtained from SIG-JN application program which is derived from NAASRA survey data. Information of inventory, condition, traffic, and the management of national roads are also featured in Web-based Geographic Information System based on the annual survey tables and diagrams. By implementing road condition data based on WebGIS in the province of West Sulawesi, It can be obtained that percentage of road conditions for excellent and unexcellent is 97.76 % and 2.24 % respectively.